Preferential expression of domain cassettes 4, 8 and 13 of Plasmodium falciparum erythrocyte membrane protein 1 in severe malaria imported in France. (March 2017) - ,; Matheron, S.; Casalino, E.; Wolff, M.; Delaval, A.; Agnamey, P.; Durand, R.; Pilo, J.E.; Rapp, C.; Faucher, J.F.; Cuisenier, B.; Poilane, I.; et al.
Abstract: Objectives: Severe Plasmodium falciparum malaria (SM) involves cytoadhesion of parasitized red blood cells, mediated by P. falciparum erythrocyte membrane protein 1, which is encoded by var genes. Expression of var gene group A and B or encoding domain cassettes DC4, DC5, DC8 and DC13 has been implicated in SM in African children, but no data exist in the context of imported malaria. The aim of this study was to investigate var gene expression linked to clinical presentation and host factors in SM imported into France. Methods: Expression level of var gene groups A, B, C, var1, var2csa, var3 and var genes encoding DC4, DC5, DC8 and DC13 was measured by quantitative RT-PCR and expressed in transcript units. Seventy SM and 48 uncomplicated malaria (UM) P. falciparum cases were analysed according to disease severity, epidemiological characteristics (migrants or travellers) and anti- P. falciparum antibodies. Cluster analysis was performed to identify gene expression profiles. Results: Var1 and B/C expression were higher in UM than SM (0.66 (0–1.1) and 1.88 (1.3–2.4); p <0.04, respectively). Group C expression differed between migrants and travellers (0.21 (0–0.75) versus 0 (0–0); p 0.002). Group A differed in naive and pre-exposed patients (1.1 (0.7–1.5) versus 0.4 (0–1.1); p 0.01). Population clusters revealed increased expression from group A and B var genes, and DC4, DC8 and DC13 in SM. Conclusions: These results corroborate the implication of DC4, DC8 and DC13 in severe imported malaria cases as African children, and their expression depends of host factors.